2017
DOI: 10.1080/19475705.2016.1161666
|View full text |Cite
|
Sign up to set email alerts
|

Studies of seismo-ionospheric correlations using anomalies in phase of very low frequency signal

Abstract: We present the results of the statistical analysis of very low frequency (VLF) signal transmitted from NWC transmitter (latitude 21.8 S, longitude 114.15 E) at 19.8 kHz received at Ionospheric and Earthquake Research Centre (IERC) (latitude 22.50 N, longitude 87.79 E). We analyse the phase of VLF signal for the whole year 2011 and compute the sunrise and sunset terminator time from it. We observe unusual shift of these sunrise and sunset terminator time during seismic events for which the earthquake epicentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 38 publications
(42 reference statements)
0
3
0
Order By: Relevance
“…Additionally, studies by Indian scientists have also reported shifts in TTs, and consequent increases in D VLF , before an impending EQ [47][48][49][50]. Many other statistical studies have also reported correlations between EQs and TT anomalies, with maximal shifts occurring 0-4 days prior to the main EQ event [47,[51][52][53][54][55][56][57][58]. Furthermore, some studies based on numerical simulation of the diurnal variation of the amplitude of the VLF signal, taking into consideration the characteristics of the VLF propagation path, the transmitter, and the receiver, are applied for the determination of TTs [50,59].…”
Section: Terminator Time Methods (Ttm)mentioning
confidence: 99%
“…Additionally, studies by Indian scientists have also reported shifts in TTs, and consequent increases in D VLF , before an impending EQ [47][48][49][50]. Many other statistical studies have also reported correlations between EQs and TT anomalies, with maximal shifts occurring 0-4 days prior to the main EQ event [47,[51][52][53][54][55][56][57][58]. Furthermore, some studies based on numerical simulation of the diurnal variation of the amplitude of the VLF signal, taking into consideration the characteristics of the VLF propagation path, the transmitter, and the receiver, are applied for the determination of TTs [50,59].…”
Section: Terminator Time Methods (Ttm)mentioning
confidence: 99%
“…By this concept several other studies have also reported shifts in TTs, and consequent increases in , before an impending EQ [Ray et al, 2013;Sasmal & Chakrabarti, 2009;Sasmal et al, 2010;Chakraborty et al, 2017]. Many other statistical studies have also reported correlations between EQs and TT anomalies, with maximal shifts occurring 0-4 days prior to the EQ [Chakrabarti et al, 2005[Chakrabarti et al, , 2007[Chakrabarti et al, , 2010Ray et al, 2010Ray et al, , 2012Ray et al, , 2013Sasmal et al, 2014;Pal et al, 2017].…”
Section: Terminator Time Methods (Ttm)mentioning
confidence: 88%
“…However, the mechanism of why the ionosphere is perturbed before an EQ, is a challenge and is poorly understood, but we show the plausible hypotheses of this LAIC process so far proposed. Emergence of lower ionospheric perturbations prior to a large EQ has already been evidenced by means of subionospheric VLF/LF propagation anomalies [129]- [137]. Because these subionospheric VLF/LF signals are known to be reflected from the lowest ionosphere (D region at day and lower E layer at night), it is already believed that the lowest ionosphere is perturbed a few days to about a week before large EQs.…”
Section: Consideration Of the Mechanism Of Ulf Depressionmentioning
confidence: 97%
“…ULF geomagnetic fluctuations depends both on the amplitude of incident wave and the parameters during their propagation in the magnetosphere/ionosphere [128]. It is not reasonable to think about the EQ effect on the equatorial plane of the magnetosphere where those pulsations are mainly generated, so it is quite natural to attribute some changes in the ground-based ULF noise to the change in the ionospheric parameter of the propagation medium as in the case of subionospheric VLF/LF (low frequency) propagation anomalies, because we already know that the lower ionosphere is definitely perturbed before major EQs [129]- [137]. Molchanov et al (2004) [120] suggested that the depression of magnetic pulsations is caused by any ionospheric disturbances before violent EQs in the following ways.…”
Section: Consideration Of the Mechanism Of Ulf Depressionmentioning
confidence: 99%